2021
DOI: 10.1002/adsc.202100631
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Reaction of α, β‐Unsaturated Ketones and 2‐Aminoaryl Alcohols for the Synthesis of 3‐Acylquinolines by a Copper Nanocatalyst

Abstract: 3‐Acylquinolines possess widespread applications in functional chemicals. However, the convenient and selective synthesis of such important substructures has to date remained a challenge. Herein, we report a method to access 3‐acylquinolines from α, β‐unsaturated ketones and 2‐aminoaryl alcohols in one pot with a copper nanocatalyst supported on nitrogen‐silica‐doped carbon (Cu/N−SiO2−C). Mechanistically, the construction of the product involves a cascade procedure including radical‐type oxidation of 2‐aminoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…[40] Meanwhile, another synthesis of quinolines 39, 40 from 2-aminobenzyl alcohols 1, 35 and enones 24 was extended (Scheme 24). [41] In this procedure, 3-acylquinolines were formed under catalysis of copper and nitrogen-silica-doped carbon (Cu/NÀ SiO 2 À C). The transformation was carried out through radical-type oxidation of 2-aminbenzyl alcohol, aza-Michael addition and annulation.…”
Section: Metal-catalyzed Synthesis Of Quinolinesmentioning
confidence: 99%
“…[40] Meanwhile, another synthesis of quinolines 39, 40 from 2-aminobenzyl alcohols 1, 35 and enones 24 was extended (Scheme 24). [41] In this procedure, 3-acylquinolines were formed under catalysis of copper and nitrogen-silica-doped carbon (Cu/NÀ SiO 2 À C). The transformation was carried out through radical-type oxidation of 2-aminbenzyl alcohol, aza-Michael addition and annulation.…”
Section: Metal-catalyzed Synthesis Of Quinolinesmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The transition-metal catalyzed dehydrogenative coupling reactions were extensively studied for the synthesis of quinolines by employing 2-aminoarylmethanols and ketones/secondary alcohols. [7][8][9][10][11][12][13][14] The transition-metals such as Ru, Ir, Cu, Mn, Co, Ni were utilized for accomplishing the synthesis of quinoline derivatives. In recent years, metal-free approaches have also been investigated for the synthesis of quinolines by using 2-aminoarylmethanols as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…To address these concerns, sustainable and atom‐economical methodologies were investigated towards the synthesis of diverse quinolines. In the past decades, the synthesis of quinolines was largely realized using 2‐aminoarylmethanols or 2‐aminoaryl carbaldehydes/2‐aminoaryl ketones in combination with ketones/secondary alcohols as precursors [7–21] . The transition‐metal catalyzed dehydrogenative coupling reactions were extensively studied for the synthesis of quinolines by employing 2‐aminoarylmethanols and ketones/secondary alcohols [7–14] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-aminobenzyl alcohols have been demonstrated to be aldehyde surrogates; therefore, Xiong et al reported the synthesis of 2-substituted-3-acylquinolines via the reaction between 2-aminobenzyl alcohols and α,β-unsaturated ketones in the presence of a copper catalyst and additives. 25 Subsequently, Yu et al demonstrated the synthesis of 3-aroylquinolines via the direct oxidative cyclocondensation of N , N ′-dimethyl enaminones with 2-aminobenzyl alcohols in the presence of potassium persulfate. 26 John et al described a [4+2] Diels Alder cycloaddition route toward 3-aroyl quinolines from enaminones and generated aza- o -quinone methides from 2-aminobenzyl chloride in situ .…”
Section: Introductionmentioning
confidence: 99%